The Effects of Dynamic Absorptive Capacity on Innovation Strategy: Evidence from SMEs in a Technological Context - Mauricio Bedoya-Villa; Elkin Pérez-Sánchez; Hugo Baier-Fuentes; Cesar Zapata-Molina; Edith Román-Castaño (Mathematics, 2023)
Absorptive capacity and innovation strategies are determining issues for the survival of organizations in current contexts. While organizations are immersed in the knowledge society, managers face great challenges to respond to market needs and performance in innovation ecosystems. This article aims to analyze the effects of absorptive capacity on the implementation of innovation strategy. A quantitative research study was conducted with a sample of 51 SMEs, and the construct model was analyzed using the SEM method. The results indicate that there is a high correlation between the level of absorptive capacity and innovation strategies. Even though firms in this specific sector work with advanced technologies, there is a basic level of development of absorptive capacity, generating some difficulties for the design and implementation of innovation strategies. Furthermore, by using the acquisition, assimilation, transformation, and exploitation of knowledge from the competitive landscape, firms improve their adaptability in the technological environment. The effects of absorptive capacity on innovation strategy contribute to the development of the extant literature on innovation management strategy and provide some managerial implications and future research areas.